Разработка и исследование сверхпроводящих СВЧ-резонаторов для электронных ускорителей - Диденко А. Н. Андрей Николаевич; Артеменко С. Н. Сергей Николаевич; Каминский В. Л. Валерий Людвигович; Новиков С. А. Сергей Автономович; Юшков Ю. Г. Юрий Георгиевич; Самойленко Г. М. Геннадий Михайлович (1985, 1985)
В фонде НТБ ТПУ отсутствует